2022
DOI: 10.3390/biology11081126
|View full text |Cite
|
Sign up to set email alerts
|

Advances on Bacterial and Fungal Biofilms for the Production of Added-Value Compounds

Abstract: In recent years, abundant research has been performed on biofilms for the production of compounds with biotechnological and industrial relevance. The use of biofilm platforms has been seen as a compelling approach to producing fine and bulk chemicals such as organic acids, alcohols, and solvents. However, the production of recombinant proteins using this system is still scarce. Biofilm reactors are known to have higher biomass density, operational stability, and potential for long-term operation than suspended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 164 publications
0
2
0
Order By: Relevance
“…Moreover, biofilms are known to provide a fitness advantage under stress and harsh conditions [ 27 ], and this property could be useful to alleviate the host metabolic burden associated with heterologous protein overproduction. Furthermore, the sessile growth may allow for reaching high biomass concentration, indeed, it has been reported that biofilm reactors can retain 5-10 times more biomass per unit volume with respect to canonical one [ 28 ], and the high plasmid maintenance in biofilm [ 29 , 30 ] could guarantee good operation stability. All these properties could be very useful in industrial processes aimed at recombinant protein production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, biofilms are known to provide a fitness advantage under stress and harsh conditions [ 27 ], and this property could be useful to alleviate the host metabolic burden associated with heterologous protein overproduction. Furthermore, the sessile growth may allow for reaching high biomass concentration, indeed, it has been reported that biofilm reactors can retain 5-10 times more biomass per unit volume with respect to canonical one [ 28 ], and the high plasmid maintenance in biofilm [ 29 , 30 ] could guarantee good operation stability. All these properties could be very useful in industrial processes aimed at recombinant protein production.…”
Section: Introductionmentioning
confidence: 99%
“…The first system for high level heterologous protein production biofilm cells was aimed at the production of eGFP in E. coli [ 33 ]. These authors demonstrated that the biofilm environment enhanced plasmid maintenance and the studies of Mergulhao and coworkers [ 28 , 32 ] showed that the GFP production levels were higher levels than their planktonic counterparts. Moreover, recently E. coli biofilm was successfully used to produce the human epidermal growth factor (hEGF) in a continuous process [ 31 ].…”
Section: Introductionmentioning
confidence: 99%